Analysis of MCFD2- and LMAN1-deficient mice demonstrates distinct functions in vivo - Zhu, Min (Blood Adv, 2018)
The LMAN1–MCFD2 complex serves as a cargo receptor for efficient transport of factor V (FV) and FVIII from the endoplasmic reticulum (ER) to the Golgi. Genetic deficiency of LMAN1 or MCFD2 in humans results in the moderate bleeding disorder combined FV and FVIII deficiency, with a similar phenotype previously observed in LMAN1-deficient mice. We now report that MCFD2-deficient mice generated by gene targeting also demonstrate reduced plasma FV and FVIII, with levels lower than those in LMAN1-deficient mice, similar to previous observations in LMAN1- and MCDF2-deficient humans. Surprisingly, FV and FVIII levels in doubly deficient mice match the higher levels observed in LMAN1-deficient mice. In contrast to the strain-specific partial lethality previously observed in LMAN1-null mice, MCFD2-null mice demonstrate normal survival in different genetic backgrounds, although doubly deficient mice exhibit partial embryonic lethality comparable to LMAN1-deficient mice. These results suggest that an alternative pathway is responsible for FV/FVIII secretion in doubly deficient mice and distinct cargo-specific functions for LMAN1 and MCFD2 within the ER-to-Golgi secretory pathway. We also observed decreased plasma levels of α1-antitrypsin (AAT) in male mice for all 3 groups of deficient mice. Comparable accumulation of AAT was observed in hepatocyte ER of singly and doubly deficient mice, demonstrating a role for LMAN1 and MCFD2 in efficient ER exit of AAT.